Service-Based Advanced Practice Providers: The Surgeon's Perspective. Issue 7 (July 2019) - Eaton, Barbara; O'Meara, Lindsay; Herrera, Anthony V.; Tesoriero, Ronald; Diaz, Jose; Bruns, Brandon
The ACGME work hour restrictions facilitated increased utilization of service-based advanced practice providers (APPs) to offset reduced general surgery resident work hours. Information regarding attending surgeon perceptions of APP impact is limited. The aim of this survey was to gauge these perceptions with respect to workload, length of stay (LOS), safety, best practice, level of function, and clinical judgment. Attending surgeons on surgical teams that employ service-based APPs at an urban tertiary referral center responded to a survey at the completion of academic year 2016. Perceptions regarding APP impact on workload, LOS, safety, best practice, level of function, and clinical judgment were examined. Twenty-two attending surgeons (40%) responded. Respondents agreed that APPs always/usually decrease their workload (77%), decrease LOS (64%), improve safety (68%), contribute to best practice (82%), and decrease near misses (71%). They also agreed that APPs decrease resident workload (87%), but fewer agreed that APPs contribute to resident education (68%). The majority perceived APPs function at the PGY1/2 (43%) or PGY3 (39%) level and always/usually trust their clinical judgment (72%), and felt there was variability in level of function among APPs (56%). This single-center study illustrates that attending surgeons perceive a positive impact on patient care by service-based APPs.